Effects of the yttria content and sintering temperature on the phase evolution in yttria-stabilized zirconia - Vavrukh, Valentyna (Видавництво Львівської політехніки, 2022)
The microstructure of YSZ ceramics stabilized by the various amount of yttria, namely 3 mol % Y2O3 (3YSZ), 4 mol% Y2O3 (4YSZ) and 5 mol % Y2O3 (5YSZ) has been studied. Three sintering temperatures, namely 1450 °C, 1500 °C and 1550 °C were used for each series of samples (3YSZ, 4YSZ, 5YSZ). The total area of the monoclinic and cubic zirconia phases in the microstructure of ceramics and the regularities of distribution of these phases were determined by ImageJ. Peculiarities of changes in volume percentage of the monoclinic and cubic phases with an increase in sintering temperature of ceramics were found. Quantitative analysis of these phases was carried out. The total distribution of the monoclinic and cubic phases by ranges of their areas was presented. Correlations between the yttria content, the sintering temperature and changes in the microstructure and phase balance of the studied ceramics were found.
Keywords: YSZ ceramics; microstructure; agglomerates of (cubic+monoclinic)-phases; sintering temperature